Modelling the thermal conductivity of (UTh-)O and (UPu-)O - Cooper,MWD; Middleburgh,SC; Grimes,RW (Journal of Nuclear Materials, 2015)
The degradation of thermal conductivity due to the non-uniform cation lattice of (UTh-)O and (UPu-)O solid solutions has been investigated by molecular dynamics, using the non-equilibrium method, from 300 to 2000 K. Degradation of thermal conductivity is predicted in (UTh-)O and (UPu-)O as compositions deviate from the pure end members: UO, PuO and ThO. The reduction in thermal conductivity is most apparent at low temperatures where phonon-defect scattering dominates over phonon–phonon interactions. The effect is greater for (UTh-)O than for (UPu-)O due to the greater mismatch in cation size and mass. Parameters for analytical expressions have been developed that describe the predicted thermal conductivities over the full temperature and compositional ranges. These expressions may be used in higher level fuel performance codes.